Identify habitat distribution within the mesoscale eddies for jumbo flying squid off Chilean waters - Wu, Xiaoci; Jin, Pengchao; Yu, Wei (Frontiers in Marine Science, 2025)
Mesoscale eddies exert profound influences on marine environments, thereby regulating habitat quality and the distribution of marine organisms. The waters off Chile are a region of intense mesoscale eddy activity and represent a major habitat for the jumbo flying squid (Dosidicus gigas), a short-lived and economically important species. However, the effects of mesoscale eddies on the habitat of D. gigas in this region remain poorly understood. In this study, we integrated autumn (March-May) fisheries data of D. gigas from 2015 to 2021 with environmental variables, including sea surface temperature (SST), chlorophyll-a concentration (Chl-a), and sea surface dissolved oxygen concentration (DO), to develop and validate habitat suitability index (HSI) models with different weighting schemes. Using the optimal HSI model in combination with mesoscale eddy data, we compared the impacts of cyclonic and anticyclonic eddies on D. gigas abundance and habitat suitability. The results revealed that the optimal HSI model effectively predicted the potential habitats of D. gigas, with weights for SIDO, SISST, and SIChl-a of 0.1, 0.1, and 0.8, respectively. Compared with anticyclonic eddies, cyclonic eddies provided broader areas of suitable habitats, characterized by suitable Chl-a and DO levels, and supported higher D. gigas abundances. Furthermore, the habitat suitability of D. gigas within mesoscale eddies exhibited interannual variability and was significantly correlated with the radius, velocity, and amplitude of the eddies. This study highlighted the critical role of mesoscale eddies in shaping the habitat suitability of D. gigas and provided valuable insights for the management and conservation of cephalopod resources.